Driving Business Performance: Cost Leadership and Government Innovation in SME Partnerships: Pengaruh Strategi Kepemimpinan Biaya dan Inovasi terhadap kinerja bisnis UMKM melalui Kemitraan UMKM - Detak Prapanca; Yani, Muhammad; Sari , Herlinda Maya Kumala; Gerung , Vido Michael; Eva, Adelia (Indonesian Journal of Law and Economics Review, 2023)
This quantitative study aims to analyze the influence of Cost Leadership Strategy and government-led innovations on business performance through SME partnerships in the Food and Beverage sector. Conducted in the Sidoarjo district of Indonesia, with a population of 49 SME groups, the research utilized a saturated sampling technique and employed a structured questionnaire to gather data. Using SEM PLS analysis, the results indicate that the Cost Leadership Strategy accounts for 44% of the business performance variance, while innovation through partnerships drives an impressive 86% impact on business performance. The findings underscore the significance of strategically fostering sustainable business performance, highlighting the role of the government in supporting SME partnerships to achieve growth and efficiency in the global marketplace. Highlights: Cost Leadership Strategy: Examining the impact of cost-focused approaches on SME business performance. Innovation in SMEs: Understanding how innovative practices contribute to business growth. Partnerships for Success: Analyzing the role of SME collaborations in driving sustainable business outcomes. Keywords: Cost Leadership Strategy, Innovation, SME Business Performance, SME Partnerships, Indonesia.